Occludin OCEL-domain interactions are required for maintenance and regulation of the tight junction barrier to macromolecular flux - Buschmann, Mary M. (The American Society for Cell Biology, 2013)
In vitro and in vivo studies implicate occludin in the regulation of paracellular macromolecular flux at steady state and in response to tumor necrosis factor (TNF). To define the roles of occludin in these processes, we established intestinal epithelia with stable occludin knockdown. Knockdown monolayers had markedly enhanced tight junction permeability to large molecules that could be modeled by size-selective channels with radii of ∼62.5 Å. TNF increased paracellular flux of large molecules in occludin-sufficient, but not occludin-deficient, monolayers. Complementation using full-length or C-terminal coiled-coil occludin/ELL domain (OCEL)–deficient enhanced green fluorescent protein (EGFP)–occludin showed that TNF-induced occludin endocytosis and barrier regulation both required the OCEL domain. Either TNF treatment or OCEL deletion accelerated EGFP-occludin fluorescence recovery after photobleaching, but TNF treatment did not affect behavior of EGFP-occludin(ΔOCEL). Further, the free OCEL domain prevented TNF-induced acceleration of occludin fluorescence recovery, occludin endocytosis, and barrier loss. OCEL mutated within a recently proposed ZO-1–binding domain (K433) could not inhibit TNF effects, but OCEL mutated within the ZO-1 SH3-GuK–binding region (K485/K488) remained functional. We conclude that OCEL-mediated occludin interactions are essential for limiting paracellular macromolecular flux. Moreover, our data implicate interactions mediated by the OCEL K433 region as an effector of TNF-induced barrier regulation.